Mitigation of heat stress-related complications by a yeast fermentate product. (August 2016) - Giblot Ducray, Henri Alexandre; Globa, Ludmila; Pustovyy, Oleg; Reeves, Stuart; Robinson, Larry; Vodyanoy, Vitaly; Sorokulova, Iryna
Abstract: Heat stress results in a multitude of biological and physiological responses which can become lethal if not properly managed. It has been shown that heat stress causes significant adverse effects in both human and animals. Different approaches have been proposed to mitigate the adverse effects caused by heat stress, among which are special diet and probiotics. We characterized the effect of the yeast fermentate EpiCor (EH) on the prevention of heat stress-related complications in rats. We found that increasing the body temperature of animals from 37.1±0.2 to 40.6±0.2 °C by exposure to heat (45 °C for 25 min) resulted in significant morphological changes in the intestine. Villi height and total mucosal thickness decreased in heat-stressed rats pre-treated with PBS in comparison with control animals not exposed to the heat. Oral treatment of rats with EH before heat stress prevented the traumatic effects of heat on the intestine. Changes in intestinal morphology of heat-stressed rats, pre-treated with PBS resulted in significant elevation of lipopolysaccharides (LPS) level in the serum of these animals. Pre-treatment with EH was effective in the prevention of LPS release into the bloodstream of heat-stressed rats. Our study revealed that elevation of body temperature also resulted in a significant increase of the concentration of vesicles released by erythrocytes in rats, pre-treated with PBS. This is an indication of a pathological impact of heat on the erythrocyte structure. Treatment of rats with EH completely protected their erythrocytes from this heat-induced pathology. Finally, exposure to heat stress conditions resulted in a significant increase of white blood cells in rats. In the group of animals pre-treated with EH before heat stress, the white blood cell count remained the same as in non-heated controls. These results showed the protective effect of the EH product in the prevention of complications, caused by heat stress. Highlights: Exposure of rats to elevated temperature results in pathological adverse effects. No adverse effects found in heat stressed rats pre-treated with yeast fermentate. Complications related to heat stress can be prevented by yeast fermentate.